A summary of intentional poisoning of Peregrine Falcons in Switzerland during the last decade - Inderwildi, Eva; Müller, Werner; Ayé, Raffael; Sinniger, Martin (Ornis Hungarica, 2018)
In May 2011, a webcam in Zurich, Switzerland, registered the sudden death of a Peregrine Falcon. Analyses revealed that poison had been applied to the nape feathers of the pigeon captured by the bird. This case really raised the awareness of Peregrine Falcon poisoning by pigeon fanciers in Switzerland. BirdLife Switzerland, with the help of numerous partners, started researches on the subject that pigeon fanciers began a “war” against Peregrine Falcons and other raptors. Between 2006 and 2017, BirdLife Switzerland listed 7 cases of proven intentional poisonings of birds of prey where analyses confirmed the use of poison; and 19 suspected cases with the presence of dead pigeons and birds of prey simultaneously or other suspicious deaths in Switzerland. Three decoy pigeons with poison on the neck could be secured before they were captured by the target species. Two pigeon fanciers who used poisoned pigeons were convicted in 2016 and 2017. Although the numbers of proven and suspected cases are still low, we believe that the phenomenon may be much more widespread. We think that the poisoning may have a negative effect on the population of the Peregrine Falcon in Switzerland.